Making Memories: An Example of the Scholarship of Teaching and Learning in Hospitality and Tourism Education. Issue 4 (2nd October 2019) - Deale, Cynthia S.
ABSTRACT: This scholarship of teaching and learning study explored students' views of their most positive, memorable learning experiences in hospitality and tourism education. A sample of 168 undergraduate hospitality management students in the United States described the positive course experiences, teaching methods, and educational activities that they believed were most memorable. The results indicate that hands-on learning experiences, authentic projects, connections with others, and selected instructor behaviors are most memorable. Implications for teaching and future research, based on the findings, are provided, as are suggestions for the use of stories and storytelling to enhance opportunities for memorable learning experiences.